2021
DOI: 10.1016/j.jbc.2021.101079
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of slit diaphragm proteins NEPHRIN and NEPH1 upon binding of HGF promotes podocyte repair

Abstract: Phosphorylation (activation) and dephosphorylation (deactivation) of the slit diaphragm proteins NEPHRIN and NEPH1 are critical for maintaining the kidney epithelial podocyte actin cytoskeleton and, therefore, proper glomerular filtration. However, the mechanisms underlying these events remain largely unknown. Here we show that NEPHRIN and NEPH1 are novel receptor proteins for hepatocyte growth factor (HGF) and can be phosphorylated independently of the mesenchymal epithelial transition receptor in a ligand-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…To look at the expression pattern of Gdf15 in podocytes during kidney injury, we made use of online available RNA sequencing data (GSE124622) and found that Gdf15 was induced by using PAN (100 µg/mL) treatment for 48 h (Figure 2A) [27,28]. Our in vitro experiments confirmed that the expression of Gdf15 in podocytes was low under physiological conditions.…”
Section: Pan Induces Gdf15 In Vitro and Gdf15 Knockout Alters Podocyt...mentioning
confidence: 53%
“…To look at the expression pattern of Gdf15 in podocytes during kidney injury, we made use of online available RNA sequencing data (GSE124622) and found that Gdf15 was induced by using PAN (100 µg/mL) treatment for 48 h (Figure 2A) [27,28]. Our in vitro experiments confirmed that the expression of Gdf15 in podocytes was low under physiological conditions.…”
Section: Pan Induces Gdf15 In Vitro and Gdf15 Knockout Alters Podocyt...mentioning
confidence: 53%
“…Nephrin is a crucial transmembrane protein located in the slit diaphragm complex. It serves as the framework for the podocyte slit diaphragm and is involved in podocyte survival [ 183 , 184 ]. Through podocin and CD2-associated protein (CD2AP), nephrin is connected to the actin cytoskeleton [ 185 , 186 ].…”
Section: Renoprotective Mechanisms Of Medicinal Plantsmentioning
confidence: 99%
“…Drosophila Enables Rapid, Scale-Able, in vivo Drug Screens Several studies have used Drosophila nephrocytes to complement a mammalian model system. One such study used a combination of in vitro podocyte and ex vivo nephrocyte models to investigate the phosphorylation of SD proteins Nephrin and NEPH1 in maintenance of the Actin cytoskeleton (Solanki et al, 2021). Fly nephrocytes were treated with hepatocyte growth factor (HGF) following chemically induced injury with protamine sulfate, which resulted in severe Actin cytoskeletal disorganization.…”
Section: Fly To Delineate the Genetic Intricacies Underlying Glomerul...mentioning
confidence: 99%